Leadership Influence on Employee Outcomes through Job Resources and Employee Engagement - Gilitwal, Bhumiphat; Amit Kumar , Amit Kumar Nag (International Journal of Psychosocial Rehabilitation, 2020)
Purpose - Organizations worldwide have started to invest resources to increase employee engagement in order to improve organizational performance. This research study attempts to investigate the influence of effective leadership on employee outcomes (job satisfaction and turnover intention) through job resources (performance feedback and social support) and employee engagement.Design/methodology/approach – A sample size of 400 employees of Thai Nippon Rubber Industry Public Company Limited who were serving for more than one year was considered, who responded to the offline questionnaire survey. Data was analyzed with linear regression analysis and ANOVA.Findings – All of the hypothesis were statistically supported. The result of this study suggested that effective leadership is a key factor in employee engagement, with both performance feedback and social support available tools that leaders can employ to drive employee engagement. It also confirmed the significance of employee engagement on job outcomes such as job satisfaction and turnover intention.Practical Implications - This study has implications on leadership training in order to focus on behavior to drive organizational strategy and goals through employee engagement. Review of the inferential data analysis shows that organizations should focus on effective leadership in order to promote employee engagement. From a leadership standpoint, it was found that performance feedback programs are the most effective, rather than social support, in employee engagement. In addition to hiring the best talent pool available, these employees need to be placed in a position to help the employees grow and drive the organization forward.